Application of software reuse concept in case-based reasoning for time tabling problem - Hong, Siaw Theng; Md Sultan, Abu Bakar (IEEE, 2011)
This paper demonstrates the application of software reuse concept together with case-based reasoning to solve time-tabling problem. The combination of both concept was induce through the similarity solution pattern which is both revise to previous cases as reference to solve current problem. A brief process flow is explained in this paper to show the possibility of combining case-based reasoning and software reuse to bring a new solution method.